High Complement Factor H-Related (FHR)-3 Levels Are Associated With the Atypical Hemolytic-Uremic Syndrome-Risk Allele CFHR3*B - Pouw, Richard B.; Gómez Delgado, Irene; López Lera, Alberto; Rodríguez de Córdoba, Santiago; Wouters, Diana; Kuijpers, Taco W.; Sánchez-Corral, Pilar (Frontiers in Immunology, 2018)
Dysregulation of the complement alternative pathway (AP) is a major pathogenic mechanism in atypical hemolytic uremic syndrome (aHUS). Genetic or acquired defects in Factor H (FH), the main AP regulator, are major aHUS drivers that associate with a poor prognosis. FH activity has been suggested to be downregulated by homologous FH-related (FHR) proteins, including FHR-3 and FHR-1. Hence, their relative levels in plasma could be disease-relevant. The genes coding for FH, FHR-3 and FHR-1 (CFH, CFHR3 and CFHR1, respectively) are polymorphic and located adjacent to each other on human chromosome 1q31.3. We have previously shown that haplotype CFH(H3)-CFHR3*B-CFHR1*B associates with aHUS and reduced FH levels. In this study, we used a specific ELISA to quantify FHR-3 in plasma samples from controls and patients with aHUS genotyped for the three known CFHR3 alleles (CFHR3*A, CFHR3*B and CFHR3*Del). In the 218 patients carrying at least one copy of CFHR3, significant differences between CFHR3 genotype groups were found, with CFHR3*A/Del patients having the lowest FHR-3 concentration (0.684-1.032 ug/mL), CFHR3*B/Del and CFHR3*A/A patients presenting intermediate levels (1.437-2.201 ug/mL), and CFHR3*A/B and CFHR3*B/B patients showing the highest concentration (2.330-4.056 ug/mL) (p<.001). These data indicate that CFHR3*A is a low-expression allele, whereas CFHR3*B, associated with increased risk of aHUS, is a high-expression allele. Our study reveals that the aHUS-risk haplotype CFH(H3)-CFHR3*B-CFHR1*B generates 2-fold more FHR-3 than the nonrisk CFH(H1)-CFHR3*A-CFHR1*A haplotype. In addition, FHR-3 levels were higher in patients with aHUS than in control individuals with the same CFHR3 genotype. These data suggest that increased plasma levels of FHR-3, altering the balance between FH and FHR-3, likely impact the FH regulatory functions and contribute to the development of aHUS.